Sodium ion battery electrolyte and preparation method and application thereof, sodium ion battery
By using sodium salt composed of sodium hexafluorophosphate and sodium bisfluorosulfonimide and electrolyte of specific organic solvents in sodium ion batteries, the poor conductivity of sodium ion batteries when using sodium ferric pyrophosphate positive electrode material and The problem of poor high-temperature cycling performance achieves efficient charging and discharge and stable cycling performance.
Patent Information
- Application Number
- CN202411068969.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-06
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-08-06
AI Technical Summary
When existing sodium ion batteries use sodium ferric pyrophosphate as the positive electrode material, conventional carbonate electrolytes have problems such as poor conductivity, low discharge specific capacity, gas production problems, fast dissolution of the interface film, and poor high-temperature circulation performance.
The sodium ion electrolyte consists of sodium hexafluorophosphate and sodium difluorosulfonimide, and organic solvents such as ethylene glycol dimethyl ether and triethyl borate. The electrolyte is improved through careful selection combination. Thermal stability and conductivity improve compatibility with hard carbon negative electrodes, and optimize the concentration and density of the electrolyte.
It significantly improves the charge and discharge efficiency, cycle stability and low-temperature discharge performance of sodium ion batteries, while reducing the cost of electrolyte, improving energy density, and reducing side reactions and material degradation.
Smart Images

Figure CN118825415B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a sodium ion battery electrolyte, a preparation method and application thereof, and a sodium ion battery. Background Art
[0002] In recent years, with the rapid development of energy storage and electric vehicle industries, the global demand for lithium has surged. In addition, the global reserves of lithium resources are limited, which has greatly restricted the development of the lithium battery industry. In this context, the resource advantages and cost advantages of sodium-ion batteries are becoming increasingly prominent. Compared with lithium-ion batteries, sodium-ion batteries still have a certain gap in energy density, but they have better low-temperature performance, safety performance and rate performance. They have broad application prospects in the field of energy storage and can form a good complementary relationship with lithium batteries.
[0003] Polyanion cathode materials have outstanding structural stability, humidity adaptability and heat resistance. When used in batteries, they have long cycle life and high safety. They are the most suitable cathode materials for energy storage sodium batteries. Sodium iron pyrophosphate is the most cost-effective type of polyanion material, and it has become increasingly popular in recent years. However, in addition to the poor conductivity and low discharge capacity of the material itself, conventional carbonate electrolytes face many problems when used in sodium iron pyrophosphate||hard carbon battery systems:
[0004] First, due to the differences between lithium and sodium themselves, the conventional carbonate formula that works well in lithium iron phosphate batteries is not fully applicable to sodium battery systems.
[0005] Secondly, the commonly used ethylene carbonate has the problem of gas production in sodium batteries. Not only that, carbonates are not well matched with hard carbon negative electrodes, and have problems with low initial efficiency and insufficient rate performance.
[0006] Third, the interfacial film in sodium electrolyte is more easily dissolved, and conventional carbonates often have a large dielectric constant, which will accelerate the dissolution of the interfacial film.
[0007] Fourth, there is a thorny problem of high-temperature cycle gas production. In addition, the sodium iron pyrophosphate battery absorbs a large amount of liquid after injecting the electrolyte, and the density of conventional electrolyte is usually 1.15-1.25g / cm 3 During this time, the battery's liquid retention capacity increases and the specific energy decreases accordingly.
[0008] In view of this, the present invention is proposed. Summary of the invention
[0009] One of the objects of the present invention is to provide a sodium ion battery electrolyte to solve at least one of the above-mentioned technical problems.
[0010] A second object of the present invention is to provide a method for preparing a sodium ion battery electrolyte.
[0011] A third object of the present invention is to provide an application of a sodium ion battery electrolyte.
[0012] A fourth object of the present invention is to provide a sodium ion battery.
[0013] In order to solve the above technical problems, the present invention particularly adopts the following technical solutions:
[0014] A first aspect of the present invention provides a sodium ion battery electrolyte consisting of a sodium salt and an organic solvent.
[0015] The sodium salts include sodium hexafluorophosphate and sodium bis(fluorosulfonyl)imide.
[0016] The organic solvent includes at least one of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, trimethyl borate, triethyl borate, tris(trimethylsilyl)borate, tris(trimethylsilyl)phosphate, vinyl sulfite and vinyl sulfate.
[0017] Furthermore, the concentration of the sodium salt is ≤0.5 mol / L, preferably 0.35 mol / L to 0.5 mol / L.
[0018] Preferably, the concentration of the sodium bis(fluorosulfonyl)imide is 0.1 mol / L to 0.2 mol / L.
[0019] Preferably, the concentration of the sodium hexafluorophosphate is 0.25 mol / L to 0.3 mol / L.
[0020] Furthermore, the organic solvent is ethylene glycol dimethyl ether, diethylene glycol dimethyl ether and triethyl borate.
[0021] Preferably, in the organic solvent, ethylene glycol dimethyl ether accounts for 25 wt.% to 45 wt.%, triethyl borate accounts for 5 wt.% to 20 wt.%, and the balance is diethylene glycol dimethyl ether.
[0022] Furthermore, in the organic solvent, ethylene glycol dimethyl ether accounts for 30 wt.% to 40 wt.%, triethyl borate accounts for 5 wt.% to 15 wt.%, and the balance is diethylene glycol dimethyl ether.
[0023] Furthermore, the density of the sodium ion battery electrolyte is ≤0.95 g / cm 3 .
[0024] The second aspect of the present invention provides a method for preparing the sodium ion battery electrolyte, which comprises dissolving the sodium salt in the organic solvent and mixing until the mixture is uniform and transparent to obtain the sodium ion battery electrolyte.
[0025] The third aspect of the present invention provides the use of the sodium ion battery electrolyte in a polyanion sodium ion battery.
[0026] A fourth aspect of the present invention provides a sodium ion battery, comprising a positive electrode, a negative electrode, a separator and the sodium ion battery electrolyte described in the first aspect.
[0027] Furthermore, the positive electrode is a polyanion positive electrode material.
[0028] The polyanionic positive electrode material includes sodium ferric pyrophosphate.
[0029] Compared with the prior art, the present invention has at least the following beneficial effects:
[0030] The sodium ion battery electrolyte provided by the present invention is composed of a sodium salt and an organic solvent. Through the carefully selected combination of the sodium salt and the organic solvent, there is no need to add additional functional additives, thereby effectively reducing the cost of the electrolyte. The combination of sodium hexafluorophosphate and sodium bis(fluorosulfonyl)imide in the sodium salt significantly improves the thermal stability and conductivity of the electrolyte. At the same time, the selected organic solvent not only has excellent solubility for the sodium salt, but also has good compatibility with the hard carbon negative electrode, providing higher interface stability. The designed electrolyte has a low concentration and low solvent viscosity, which further optimizes the fluidity of the electrolyte, so that it can achieve a good wetting effect on the battery pole piece and the diaphragm surface. This high fluidity and low desolvation energy barrier ensure that the ions in the electrolyte can quickly reach the electrode surface and complete the interface reaction and transfer, effectively participate in the electrochemical reaction, thereby significantly improving the charge and discharge efficiency of the sodium ion battery. Through this design, the electrolyte of the present invention achieves dual optimization of cost-effectiveness and battery performance without sacrificing performance.
[0031] The method for preparing the sodium ion battery electrolyte provided by the present invention has a simple process, improves production efficiency, reduces production costs, and improves the feasibility of large-scale production.
[0032] The application of the sodium ion battery electrolyte provided by the present invention in a polyanion sodium ion battery, in view of the advantages of the above-mentioned sodium ion battery electrolyte, makes the electrolyte compatible with the chemical properties of the electrode material, reduces the occurrence of interfacial reactions, thereby reducing side reactions and material degradation during the operation of the battery, thereby significantly improving the overall performance of the sodium ion battery.
[0033] The sodium ion battery provided by the present invention, in view of the advantages of the above-mentioned sodium ion battery electrolyte, enables the prepared sodium ion battery to significantly improve the cycle stability of the battery not only under normal temperature conditions but also under a high temperature environment of 45°C, and can also improve the discharge performance of the battery at -40°C. Compared with sodium ion batteries using traditional electrolytes, the battery of the present invention has achieved a significant leap in cycle performance. In addition, the low-density characteristics of this electrolyte enable the energy density of the battery to be increased by 6% under the same injection volume without sacrificing the volume or weight of the battery. This increase in energy density not only enhances the battery's endurance, but also provides greater flexibility for battery design and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0035] Figure 1 This is the normal temperature cycle performance diagram obtained in Test Example 2;
[0036] Figure 2 This is the 45°C cycle performance diagram obtained in Experimental Example 3. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. The components of the embodiments of the present invention described and shown herein can be arranged and designed in various different configurations.
[0038] A first aspect of the present invention provides a sodium ion battery electrolyte consisting of a sodium salt and an organic solvent.
[0039] The sodium salts include sodium hexafluorophosphate and sodium bis(fluorosulfonyl)imide.
[0040] The organic solvent includes at least one of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, trimethyl borate, triethyl borate, tris(trimethylsilyl)borate, tris(trimethylsilyl)phosphate, vinyl sulfite and vinyl sulfate.
[0041] The sodium ion battery electrolyte provided by the present invention is composed of a sodium salt and an organic solvent. Through the carefully selected combination of the sodium salt and the organic solvent, there is no need to add additional functional additives, thereby effectively reducing the cost of the electrolyte. The combination of sodium hexafluorophosphate and sodium bis(fluorosulfonyl)imide in the sodium salt significantly improves the thermal stability and conductivity of the electrolyte. At the same time, the selected organic solvent not only has excellent solubility for the sodium salt, but also has good compatibility with the hard carbon negative electrode, providing higher interface stability. The designed electrolyte has a low concentration and low solvent viscosity, which further optimizes the fluidity of the electrolyte, so that it can achieve a good wetting effect on the battery pole piece and the diaphragm surface. This high fluidity and low desolvation energy barrier ensure that the ions in the electrolyte can quickly reach the electrode surface and complete the interface reaction and transfer, effectively participate in the electrochemical reaction, thereby significantly improving the charge and discharge efficiency of the sodium ion battery. Through this design, the electrolyte of the present invention achieves dual optimization of cost-effectiveness and battery performance without sacrificing performance.
[0042] Specifically, sodium bis(fluorosulfonyl)imide can not only improve the intrinsic thermal stability and electrical conductivity of the electrolyte, but also derive an inorganic-rich interface film during the charge and discharge process, which is of great help in improving the high-temperature performance of sodium-ion batteries. In addition, thanks to the low content of sodium hexafluorophosphate in the electrolyte, the overall hexafluorophosphate content of the electrolyte is low, which is beneficial to the chemical stability of the electrolyte itself.
[0043] The solvation sheath formed by ether solvents in organic solvents undergoes a faster desolvation process at the electrolyte-electrode interface, which gives ether electrolytes excellent kinetic properties.
[0044] Furthermore, the concentration of the sodium salt is ≤0.5 mol / L, preferably 0.35 mol / L to 0.5 mol / L.
[0045] The sodium salt concentration has a direct impact on the viscosity and fluidity of the electrolyte. When the concentration is within the range of 0.35mol / L to 0.5mol / L, the electrolyte achieves a good balance between conductivity and low viscosity, which not only fully wets the electrodes and diaphragms, but also ensures efficient electrode interface reactions.
[0046] In the concentration range of 0.35mol / L to 0.5mol / L, the acidity and corrosiveness of the electrolyte can also be reduced, reducing the potential safety hazards of the battery during use. Especially in high temperature environments, when sodium hexafluorophosphate is used as sodium salt, the concentration of the sodium salt will affect the intrinsic chemical stability and thermal stability of the electrolyte. This concentration range helps to maintain the stability of the electrolyte and extend the storage time of the electrolyte.
[0047] If the concentration of sodium salt is higher than 0.5 mol / L, the room temperature and 45°C cycle performance of sodium ion batteries will not be significantly improved, the low temperature discharge performance will deteriorate, and the electrolyte cost will also increase; if the concentration of sodium salt is lower than 0.35 mol / L, the room temperature cycle performance and rate performance of sodium ion batteries will be adversely affected due to the low conductivity and insufficient film formation of sodium salt anions.
[0048] Typically but not limiting, the concentration of the sodium salt can be, for example, 0.35 mol / L, 0.375 mol / L, 0.40 mol / L, 0.425 mol / L, 0.45 mol / L, 0.475 mol / L or 0.5 mol / L, or any value within the range of 0.35 mol / L to 0.5 mol / L.
[0049] Preferably, the concentration of the sodium bis(fluorosulfonyl)imide is 0.1 mol / L to 0.2 mol / L.
[0050] Typically but not limiting, the concentration of sodium bis(fluorosulfonyl)imide may be, for example, 0.1 mol / L, 0.125 mol / L, 0.15 mol / L, 0.175 mol / L or 0.2 mol / L, or any value within the range of 0.1 mol / L to 0.2 mol / L.
[0051] Preferably, the concentration of the sodium hexafluorophosphate is 0.25 mol / L to 0.3 mol / L.
[0052] Typically but not limiting, the concentration of sodium hexafluorophosphate can be, for example, 0.25 mol / L, 0.26 mol / L, 0.27 mol / L, 0.28 mol / L, 0.29 mol / L, 0.3 mol / L, or any value within the range of 0.25 mol / L to 0.3 mol / L.
[0053] Furthermore, the organic solvent is ethylene glycol dimethyl ether, diethylene glycol dimethyl ether and triethyl borate.
[0054] Triethyl borate has the characteristics of wide liquid range and low density. When used as an organic solvent, it can not only reduce the NaF content in the interface film and thus reduce the internal resistance, but also promote the dissolution of sodium salt at low temperatures.
[0055] Preferably, in the organic solvent, ethylene glycol dimethyl ether accounts for 25 wt.% to 45 wt.%, triethyl borate accounts for 5 wt.% to 20 wt.%, and the balance is diethylene glycol dimethyl ether.
[0056] Due to the disadvantage of low flash point, if the proportion of ethylene glycol dimethyl ether in organic solvent is greater than 45wt.%, the overall safety of the electrolyte will be reduced. However, it also has the advantages of ultra-low viscosity, low density and strong ability to dissolve sodium salts. When the dosage is less than 25wt.%, it cannot effectively improve the viscosity and fluidity of the electrolyte and reduce the overall density of the electrolyte.
[0057] Diethylene glycol dimethyl ether has good comprehensive performance and no obvious disadvantages, and is used as a solvent base. When triethyl borate accounts for more than 20wt.%, the high temperature cycle performance of the battery decreases. If the proportion is less than 5wt.%, the internal resistance optimization effect on the interface film is not obvious.
[0058] Furthermore, in the organic solvent, ethylene glycol dimethyl ether accounts for 30 wt.% to 40 wt.%, triethyl borate accounts for 5 wt.% to 15 wt.%, and the balance is diethylene glycol dimethyl ether.
[0059] Typically but not limiting, in the organic solvent, the proportion of ethylene glycol dimethyl ether can be, for example, 25wt.%, 30wt.%, 35wt.%, 40wt.% or 45wt.%, or any value within the range of 25wt.% to 45wt.%; the proportion of triethyl borate can be, for example, 5wt.%, 10wt.%, 15wt.% or 20wt.%, or any value within the range of 5wt.% to 20wt.%. The balance is made up of diethylene glycol dimethyl ether to ensure that the total weight percentage of the entire organic solvent system reaches 100%.
[0060] Furthermore, the density of the sodium ion battery electrolyte is ≤0.95 g / cm 3 .
[0061] The sodium ion electrolyte of the present invention has low concentration, low solvent viscosity and wide liquid range, so the electrolyte has low intrinsic viscosity, good wettability and fluidity, and exhibits good low-temperature performance.
[0062] The second aspect of the present invention provides a method for preparing the sodium ion battery electrolyte, which comprises dissolving the sodium salt in the organic solvent and mixing until the mixture is uniform and transparent to obtain the sodium ion battery electrolyte.
[0063] The method for preparing the sodium ion battery electrolyte provided by the present invention has a simple process, improves production efficiency, reduces production costs, and improves the feasibility of large-scale production.
[0064] The third aspect of the present invention provides the use of the sodium ion battery electrolyte in a polyanion sodium ion battery.
[0065] The application of the sodium ion battery electrolyte provided by the present invention in a polyanion sodium ion battery, in view of the advantages of the above-mentioned sodium ion battery electrolyte, makes the electrolyte compatible with the chemical properties of the electrode material, reduces the occurrence of interfacial reactions, thereby reducing side reactions and material degradation during the operation of the battery, thereby significantly improving the overall performance of the sodium ion battery.
[0066] A fourth aspect of the present invention provides a sodium ion battery, comprising a positive electrode, a negative electrode, a separator and the sodium ion battery electrolyte described in the first aspect.
[0067] The sodium ion battery provided by the present invention, in view of the advantages of the above-mentioned sodium ion battery electrolyte, enables the prepared sodium ion battery to significantly improve the cycle stability of the battery not only under normal temperature conditions but also under a high temperature environment of 45°C, and can also improve the discharge performance of the battery at -40°C. Compared with sodium ion batteries using traditional electrolytes, the battery of the present invention has achieved a significant leap in cycle performance. In addition, the low-density characteristics of this electrolyte enable the energy density of the battery to be increased by 6% under the same injection volume without sacrificing the volume or weight of the battery. This increase in energy density not only enhances the battery's endurance, but also provides greater flexibility for battery design and application.
[0068] Furthermore, the positive electrode is a polyanion positive electrode material.
[0069] The polyanionic positive electrode material includes sodium ferric pyrophosphate.
[0070] In the following, some embodiments of the present invention are described in detail in conjunction with the embodiments. In the absence of conflict, the following embodiments and the features in the embodiments can be combined with each other. The raw materials used in the present invention can be obtained by commercial purchase unless otherwise specified.
[0071] In the following examples and comparative examples, ethylene glycol dimethyl ether is represented by DME, diethylene glycol dimethyl ether is represented by DEGDME, triethyl borate is represented by TEB, trimethyl borate is represented by TMB, ethylene carbonate is represented by EC, propylene carbonate is represented by PC, and ethyl methyl carbonate is represented by EMC. In addition, NaPF6 is sodium hexafluorophosphate, NaFSI is sodium bis(trifluoromethyl)sulfonyl imide, NaTFSI is sodium bis(trifluoromethyl)sulfonyl imide, NaDFOB is sodium difluorooxalatoborate, M represents mol / L, and "\" represents untested.
[0072] The formulations of the embodiments and comparative examples are shown in Table 1 below.
[0073] Table 1
[0074]
[0075]
[0076] The preparation methods of the electrolytes of the embodiments and comparative examples are as follows:
[0077] In an argon atmosphere glove box with a water content of <0.1ppm and an oxygen content of <0.1ppm, the organic solvents were mixed and shaken and refrigerated for more than 12 hours, and sodium salts were added to the refrigerated solvents respectively, followed by stirring at room temperature for 3 hours to obtain a uniform and transparent sodium ion electrolyte.
[0078] Test Example 1
[0079] Preparation of sodium ion soft-pack batteries: Sodium iron pyrophosphate Na4Fe3(PO4)2P2O7 is used as the positive electrode material, hard carbon is used as the negative electrode material, and polyethylene film is used as the separator to assemble sodium ion soft-pack batteries with a designed battery capacity of 1.5Ah.
[0080] Test Example 2
[0081] Sodium ion battery room temperature cycle experiment: Use the sodium ion soft pack described in Test Example 1, inject the sodium ion electrolyte obtained in Examples 1-9 and Comparative Examples 1-5 at an injection volume of 7g / Ah and complete the packaging, then let it stand at room temperature for 48 hours. After the standing period, the battery is formed at room temperature and in a voltage range of 1.5-3.65V at a rate of 0.2C. After the formation is completed, the battery is sealed and aged again. After the aging is completed, the battery is placed in a charge and discharge tester for charge and discharge cycle testing. The test conditions are: room temperature environment, voltage range 1.5-3.65V, and charge and discharge rate 1C. The data obtained are shown in Table 1.
[0082] The data obtained from the room temperature cycle performance process obtained in Example 5 and Comparative Example 1 are plotted to obtain Figure 1 .
[0083] Test Example 3
[0084] Sodium ion battery 45°C cycle test: Different from Test Example 2, the ambient temperature of the sodium ion battery test is 45°C, and the other parameters are consistent with Test Example 2. The test results are shown in Table 1.
[0085] The data obtained from the 45°C cycle performance process obtained in Example 5 and Comparative Example 1 are plotted to obtain Figure 2 .
[0086] As can be seen from Table 1, from the data of Comparative Examples 2, 3 and 4, it can be found that the room temperature cycle capacity retention rate of the battery increases with the increase of electrolyte concentration, but after increasing to 0.45 mol / L, continuing to increase the concentration has no obvious effect on improving the cycle performance, but will increase the cost and viscosity of the electrolyte.
[0087] Comparing Comparative Example 3 and Comparative Example 5, it can be seen that sodium bis(fluorosulfonyl)imide as a secondary salt can greatly improve the high-temperature cycle performance of the battery cell, but it can also have an adverse effect on the normal-temperature cycle performance of the battery cell. Comparing the capacity retention rates of Example 1 and Comparative Example 5, it can be seen that triethyl borate can greatly inhibit the adverse effects of sodium bis(fluorosulfonyl)imide on the normal-temperature cycle performance of the battery cell, while also improving the high-temperature cycle stability of the degraded electrolyte when applied to the battery cell.
[0088] By comparing the capacity retention rates of Example 1, Example 2, and Example 3, it can be found that 0.15 mol / L is the optimal concentration of sodium bis(fluorosulfonyl)imide added to the electrolyte. If the concentration is higher than this, the high-temperature cycle performance of the measured battery cell will not be significantly further improved, but will cause greater damage to the room-temperature cycle performance of the battery cell.
[0089] By comparing the capacity retention rates of Example 2 and Example 4, it is found that the change in the ratio of ethylene glycol dimethyl ether to diethylene glycol dimethyl ether will not significantly affect the cycle performance of the battery cell, but from the perspective of density and viscosity, the ratio of the two corresponding to Example 2 is better.
[0090] Example 2, Example 5, and Example 6 are experimental groups conducted to explore the optimal dosage of triethyl borate. The experimental data show that when triethyl borate accounts for 10% of the total mass of the solvent, the performance of the battery cell in both room temperature cycle and high temperature cycle is more balanced. By comparing the capacity retention rates of Example 5, Example 7, Example 8, and Example 9, it can be further determined that the combination of sodium bis(fluorosulfonyl)imide, triethyl borate, and sodium hexafluorophosphate + ether electrolyte system has the best effect.
[0091] Finally, from Figure 2 It can be seen that the capacity retention rates of Comparative Example 5 and Comparative Example 1 show that when the sodium ion electrolyte provided by the present invention is applied to a sodium ion battery, the cycle performance is much better than that of a conventional ester electrolyte.
[0092] Test Example 4
[0093] The density of the sodium ion electrolyte prepared in Example 5 and Comparative Example 1 and the liquid retention coefficient after being injected into the battery core were tested, and the obtained data are shown in Table 2.
[0094] It should be noted that the liquid retention volume refers to the difference between the mass of the battery after the second sealing process (including the air bag) and the mass before the injection of electrolyte, and the liquid retention coefficient is the ratio of the liquid retention volume to the battery cell capacity.
[0095] Using the sodium ion soft-pack battery described in Test Example 1, the same mass of the sodium ion electrolyte of the embodiment and the comparative example was respectively injected into the soft-pack battery according to the injection coefficient standard of 7 g / Ah to carry out a liquid retention coefficient measurement experiment.
[0096] Table 2
[0097]
[0098] From the density test results in Table 2, it can be seen that the density of the sodium ion electrolyte in Comparative Example 1 is 1.19 g / cm 3 , while the density of the sodium ion electrolyte in Example 5 is only 0.946 g / cm 3 In terms of calculation of the liquid retention coefficient, the liquid retention coefficient corresponding to the sodium ion electrolyte of Example 5 is only 5.15 g / Ah, which is significantly lower than the liquid retention coefficient corresponding to the sodium ion electrolyte of Comparative Example 1. Thanks to the lower liquid retention, it is calculated that compared with conventional ester electrolytes such as Comparative Example 1, the use of the low-density electrolyte of Example 5 can increase the energy density of the battery cell by about 6%.
[0099] Test Example 5
[0100] Sodium ion battery low temperature discharge experiment: Use the sodium ion soft pack described in Test Example 1, inject the sodium ion electrolyte obtained in Examples 1, 2, 4, 5 and Comparative Examples 1, 3, 4, 5 at an injection volume of 7g / Ah and complete the packaging, and then let it stand at room temperature for 48 hours. After standing, the battery is formed at a rate of 0.2C at room temperature in a voltage range of 1.5-3.65V. After the formation is completed, the battery is sealed and aged again. After the aging is completed, the battery is charged to 3.65V at a rate of 1C, and then placed in a low temperature test box (-40°C) for 3 hours, and then discharged to 1.5V at a rate of 0.5C. The low temperature performance of the electrolyte is judged by the ratio of the discharge capacity of the battery at -40°C to the charging capacity at room temperature. The data obtained are shown in Table 3.
[0101] Table 3
[0102] Serial number Electrolyte formula Low temperature performance% Example 1 <![CDATA[0.35M NaPF6+0.1M NaFSI-DME / DEGDME / TEB(40:55:5)]]> 61.1 Example 2 <![CDATA[0.3M NaPF6+0.15M NaFSI-DME / DEGDME / TEB(40:55:5)]]> 61.5 Example 4 <![CDATA[0.3M NaPF6+0.15M NaFSI-DME / DEGDME / TEB(30:65:5)]]> 59.2 Example 5 <![CDATA[0.3M NaPF6+0.15M NaFSI-DME / DEGDME / TEB(40:50:10)]]> 62.3 Comparative Example 1 <![CDATA[1.0M NaPF6-PC / EMC(1:1,W)+1.5wt%FEC+1.0wt%PS]]> 55.2 Comparative Example 3 <![CDATA[0.45M NaPF6-DME / DEGDME(40:60)]]> 58.5 Comparative Example 4 <![CDATA[0.7M NaPF6-DME / DEGDME(40:60)]]> 52.3 Comparative Example 5 <![CDATA[0.35M NaPF6+0.1M NaFSI-DME / DEGDME(40:60)]]> 59.8
[0103] It can be seen from the low temperature test data in Table 3 that when the sodium ion electrolyte of Comparative Example 1 is used, the ratio of the discharge capacity of the sodium ion battery at -40°C to the charge capacity at room temperature is 55.2%, while the ratio corresponding to the sodium ion electrolyte of the preferred embodiment 5 is 62.3%, indicating that the sodium ion electrolyte provided by the present invention has better low temperature performance than conventional ester electrolytes. In addition, by comparing Comparative Example 3 and Comparative Example 4, it is found that when the electrolyte concentration is increased from 0.45mol / L to 0.7mol / L, the low temperature discharge performance of the battery cell is significantly deteriorated. Combined with the previous cycle test results, 0.45mol / L is determined to be the relative optimal concentration. Comparing Comparative Example 5 with Example 1, Example 2 and Example 5, it is found that the introduction of triethyl borate in an appropriate amount can improve the low temperature discharge performance of the battery cell. Comparing Comparative Example 3 with Comparative Example 5, and Example 1 with Example 2, it can be seen that reducing the concentration of sodium hexafluorophosphate within a certain concentration range and introducing sodium bis(fluorosulfonyl)imide is beneficial to low temperature performance, which is attributed to the excellent dissociation degree of sodium bis(fluorosulfonyl)imide at low temperatures. Further comparison of Example 2 with Example 4 shows that when the proportion of ethylene glycol dimethyl ether in the electrolyte decreases, the low temperature performance of the battery cell deteriorates.
[0104] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A sodium ion battery electrolyte, characterized in that: It is composed of sodium salt and organic solvent; The sodium salts are sodium hexafluorophosphate and sodium bis(fluorosulfonyl)imide; The organic solvent is ethylene glycol dimethyl ether, diethylene glycol dimethyl ether and triethyl borate; Among them, the proportion of ethylene glycol dimethyl ether is 25wt.%~45wt.%, the proportion of triethyl borate is 5wt.%~20wt.%, and the balance is diethylene glycol dimethyl ether; the concentration of the sodium salt is <0.5mol / L; The concentration of the sodium bis(fluorosulfonyl)imide is 0.1 mol / L to 0.2 mol / L; The concentration of the sodium hexafluorophosphate is 0.25 mol / L to 0.3 mol / L; The density of the sodium ion battery electrolyte is ≤0.95g / cm 3 .
2. The sodium ion battery electrolyte according to claim 1, characterized in that In the organic solvent, ethylene glycol dimethyl ether accounts for 30wt.% to 40wt.%, triethyl borate accounts for 5wt.% to 15wt.%, and the balance is diethylene glycol dimethyl ether.
3. A method for preparing a sodium ion battery electrolyte according to claim 1 or 2, characterized in that: The sodium salt is dissolved in the organic solvent and mixed until uniform and transparent to obtain the sodium ion battery electrolyte.
4. Use of the sodium ion battery electrolyte according to claim 1 or 2 in a polyanion sodium ion battery.
5. A sodium ion battery, characterized in that: It comprises a positive electrode, a negative electrode, a separator and the sodium ion battery electrolyte according to claim 1 or 2.
6. The sodium ion battery according to claim 5, characterized in that: The positive electrode is a polyanion positive electrode material; The polyanionic positive electrode material includes sodium ferric pyrophosphate.
Citation Information
Patent Citations
Electrolyte compositions
WO2022238985A2
Sodium ion battery
WO2024131352A1